How sufficient economy philosophy contributes to sustainable resilience: a qualitative study on the COVID-19 pandemic response in Thailand - Viroj Tangcharoensathien; Kathleen Ford; Bhubate Samutachak; Kullatip Satararuji (BMJ Open)
Objective This qualitative study sought to understand how sufficient economy philosophy (SEP) was applied to cope with and recover from the COVID-19 pandemic.Design A qualitative study conducted through focus group discussions.Participants 19 focus groups, with 161 participants, selected for the diverse backgrounds in gender, profession, education and region (urban/rural) and different levels of impact from the pandemic.Setting Bangkok, the capital city, and the four regions of Thailand: north, northeast, south and central.Findings Participants highlighted the moderation, reasonableness and prudence as key themes that mitigated adverse economic impacts during the pandemic. Communities practising the SEP reported resilience through balanced consumption, prudent planning and social cooperation. Many participants mentioned that the SEP was crucial to their survival and should have been better practised. Though the market structure failed during the pandemic, they still could secure the essential items to maintain livelihood.Conclusion In a society where changes are complicated by multiple factors, crises may occur more frequently, unsuspectedly and in various forms. Tools and a mechanism for resilience are increasingly needed. This study highlights the importance of the SEP, which incorporates five key concepts: moderation, reasonableness, prudence, knowledge and morality. These concepts help affected communities survive and become resilient, which is crucial for achieving several Sustainable Development Goals, such as poverty and hunger reduction, enhanced health and well-being and the sustainability of cities and communities.